Validity, inter-and intra-reliability of new equipment innovation for increasing lung volume training and measuring chest expansion measurement among healthy people - Decha Pinkaew (2020)
© 2019, Indian Journal of Public Health Research and Development. All rights reserved. Objective The purposes of this study were to investigate the validity and reliability of new equipment innovation for increasing lung volume training and measuring chest expansion in healthy people. Method This study considered 30 healthy participants (15 male, 15 female) who were aged between 18 to 70 years (47.23± 19.29 years). The chest expansion measurements were taken with cloth tape measurement at 3 levels of the rib cage (upper, middle and lower levels). The lung volume training was determined by intensive spirometer (vodylne). The new equipment innovation was investigated through chest expansion and lung volume. Results The pearson’s correlation analysis was performed to establish the validity of cloth tape and new equipment innovation. The study findings suggested that the investigated measurement tools were significantly correlate with the upper, middle and lower chest level chest expansion and lung volume considering (r = 0.898, r = 0.925 and r = 0.896, p < 0.05, respectively). Moreover, validity of new equipment innovation and vodylne showed significantly good correlation in upper, middle and lower chest level (r = 0.668, r = 0.689 and r = 0.734, p < 0.05, respectively). Intra-class Correlation Coefficient (ICC) values for intra-rater reliability in upper, middle and lower chest part were 0.958, 0.979 and 0.976, respectively. Inter-rater reliability ICCs in upper, middle and lower chest part were 0.922, 0.959 and 0.944 that showed high reliability. Conclusion A new equipment innovation for increasing lung volume training and measuring chest expansion was valid and reliable considering intra-item and inter-item correlation. However, it might for lung volume training and measuring chest expansion.